Irrational use of antibiotics in India: Time to work together - Rafeeque, MBBS, MD, Dr. M. (Journal of Pharmacy Practice and Community Medicine)
Antimicrobial resistance is the major public health problem in India due to higher incidence of inappropriate use of antibiotics.[1] India has been reported as a country with one of the number of tropical infectious disease. Recent reports have shown an inappropriate use of antimicrobial agents against these diseases, which has led to increase in microbial resistance.[2,3]